WHAT IS THE AWARENESS LEVEL OF RHEUMATOLOGY PATIENTS, PHYSICIANS AND OTHER HEALTH CARE PROFESSIONALS ABOUT VACCINATION IN RHEUMATOLOGY? DOES EDUCATION CONTRIBUTE TO INCREASING AWARENESS? - Avsar, A. Koeken; Kenar, G.; Erpek, E.; Akar, S.; Gundz, O. Soysal; Acar, E. A.; Onen, F. (Elsevier, 2024)
[Abstract Not Available]
Meeting of the European-Alliance-of-Associations-for-Rheumatology (EULAR) -- JUN 12-15, 2024 -- Vienna, AUSTRIA
Keywords: biological DMARD; Vaccination/Immunization